Astrophysically useful parameters for certain band systems of BeH, BeD and BeT molecules - Shanmugavel R. (Serbian Astronomical Journal, 2006)
The vibronic (vibration-electronic) transition probability parameters such as Franck-Condon (FC) factors and r-centroids of diatomic molecular species could be useful in the identification of molecular bands and in the estimation of relative abundance of the emitted species in astrophysical sources. In this study, they have been evaluated for the electronic transitions A2Πr-X2Σ+, B2Πr-X2Σ+ and C2Σ+ - X2Σ+ systems of BeH, A2Πr - X2Σ and C2Σ+ - X2Σ+ system of BeD and A2Πr - X2Σ+ system of BeT molecules using a suitable potential.